The activities of the community schools of Cagayan district in relation to education, health and recreation - Buenafe, Laurie Carino 1921- (1972)
The study is designed to identify the activities of the community schools of Caoayan District in relation to education, health and recreation. The activities of the community school aims at the improvement of all phases of living. It concerns itself with the needs and problems of the people in the rural areas and attacks those problems through three areas namely: education, health, and recreation.
Thesis (M. Ed.)--University of the Philippines, Diliman.
Keywords: Community and school; Education -- Philippines -- Cagayan (Ilocos Sur).